Mechanical nociceptive thresholds using four probe configurations in horses - Taylor, Polly M.; Crosignani, Nadia [UNESP]; Lopes, Carlize [UNESP]; Rosa, Ademir C. [UNESP]; Luna, Stelio P. [UNESP]; Puoli Filho, José N. [UNESP] (Association of Veterinary Anaesthetists and the American College of Veterinary Anesthesia and Analgesia, 2015)
To examine the relationship between probe tip size and force readings of mechanical nociceptive thresholds (MTs) to identify appropriate probes for horses. Randomized, crossover study. Eight adult, mixed-breed horses aged 5-10 years, weighing 268-460 kg. Four probe configurations (PCs) were used in random sequence: 1.0 mm diameter (SHARP); 3.2 mm (BLUNT); spring-mounted 1.0 mm (SPRING), and 3 × 2.5 mm (3PIN). A remote-controlled unit on the horse increased force (1.2 N second(-1) ) in a pneumatic actuator on the metacarpus. Mean MT for each PC was calculated from 10 readings for each horse. Data were log-transformed for analysis using mixed-effects anova/linear regression (p < 0.05). Variability of data for each PC was assessed using the coefficient of variation (CV). Mean ± standard deviation MTs were: SHARP, 5.6 ± 2.3 N; BLUNT, 11.4 ± 3.4 N; 3PIN, 9.6 ± 4.6 N, and SPRING 6.4 ± 1.8 N. Mean MT for SHARP was significantly lower than for BLUNT (p < 0.001) and 3PIN (p < 0.001), but not different from SPRING (p > 0.05). Mean MT was significantly higher for BLUNT than for 3PIN (p < 0.05) and SPRING (p < 0.001). Mean MT for 3PIN was significantly higher than for SPRING (p < 0.001). Larger contact area PCs produced higher MTs than smaller PCs, but the relationship was not linear. BLUNT (area: 10-fold greater) gave a MT two-fold higher than SHARP. 3PIN (area: 20-fold greater) produced more variable MTs, less than two-fold higher than SHARP. SPRING was similar to SHARP. CVs were: SHARP, 22.9%; BLUNT, 72.3%; 3PIN, 44.2%, and SPRING, 28.7%. The PC has nonlinear effects on MT. Therefore, it is important to define PC when measuring MT. Smaller probe tips may be preferable as MT data are less variable.
Keywords: Force; Nociception; Pain; Pressure; Probe size; Stimulus intensity